2016
DOI: 10.1002/acp.3256
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Depictive Versus Tracing Gestures Selectively Aids Verbal Versus Visual–Spatial Learning in Primary School Children

Abstract: Previous research has established that gesture observation aids learning in children. The current study examined whether observation of gestures (i.e. depictive and tracing gestures) differentially affected verbal and visual-spatial retention when learning a route and its street names. Specifically, we explored whether children (n = 97) with lower visual and verbal workingmemory capacity benefited more from observing gestures as compared with children who score higher on these traits. To this end, 11-to 13-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Individual differences in verbal (e.g., digit span task; Kartalkanat and Göksun, 2020), visual (e.g., visual patterns task;van Wermeskerken et al, 2016), or general WM capacity (e.g., operation span task; Yeo and Tzeng, 2019) did not predict how much children benefited from observing gestures for learning. There was hardly any variance in WM capacity in most of these studies (e.g., van Wermeskerken et al, 2016). This might obscure the otherwise possible effects of different WM capacities on the values of observing gestures in children.…”
Section: Individual Differences In Gesture Processing In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual differences in verbal (e.g., digit span task; Kartalkanat and Göksun, 2020), visual (e.g., visual patterns task;van Wermeskerken et al, 2016), or general WM capacity (e.g., operation span task; Yeo and Tzeng, 2019) did not predict how much children benefited from observing gestures for learning. There was hardly any variance in WM capacity in most of these studies (e.g., van Wermeskerken et al, 2016). This might obscure the otherwise possible effects of different WM capacities on the values of observing gestures in children.…”
Section: Individual Differences In Gesture Processing In Childrenmentioning
confidence: 99%
“…Not all children benefit from visual aids such as diagrammatical illustrations when learning math (e.g., (Cooper et al, 2017). Indeed, observing gestures does not assist all children's comprehension of narratives or learning new skills (e.g., Church et al, 2004;van Wermeskerken et al, 2016;Yeo and Tzeng, 2019;Bohn et al, 2020;Kartalkanat and Göksun, 2020). Kartalkanat and Göksun (2020) found a positive relationship with verbal skills and the beneficial effects of observing gestures, preschoolers with higher expressive language ability benefited more from observing iconic gestures in the encoding of spatial events.…”
Section: Individual Differences In Gesture Processing In Childrenmentioning
confidence: 99%
“…Brucker et al, 2015 ; Castro-Alonso, Ayres, & Paas, 2015 ; Fiorella & Mayer, 2016 ; Rueckert, Church, Avila, & Trejo, 2017 ) or with non-human movements (Pouw, van Gog, et al, 2016 ) in recent studies. Some studies have revealed moderating factors or boundary conditions of presenting movements, such as the congruency between the learners’ perspective and the perspective depicted in the learning materials (Fiorella, van Gog, Hoogerheide, & Mayer, 2016 ), learners’ gender (Wong, Castro-Alonso, Ayres, & Paas, 2015 ), and the depicted movement type (van Wermeskerken, Fijan, Eielts, & Pouw, 2016 ). A small number of recently published studies brought about results indicating no effects for observed movements (e.g.…”
Section: Reviewmentioning
confidence: 99%
“…Other work has found that college students benefit from observing iconic gestures when learning statistics (Rueckert et al, 2017). Furthermore, deictic and iconic gestures can help both children and adults learn to perform spatial tasks (Austin et al, 2018; Van Wermeskerken et al, 2016). Finally, studies with college students have found that natural gestures (Mayer & DaPra, 2012; Wang et al, 2018) and pointing (i.e., deictic) gestures (Li et al, 2019; Mayer & DaPra, 2012; Wang et al, 2018) directed attention to relevant task material and improved learning (although see Ouwehand et al, 2015 for an exception).…”
Section: Introductionmentioning
confidence: 99%